PENGARUH MOTIVASI KERJA, SELF EFFICACY, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA LPD DESA DALUNG - Ayu Putu Ita Rismawati; I Nengah Suardika; Putu Agus Eka Rismawan (VALUES, 2023)
Employee performance is a very important thing in an organization. Factors that influence employee performance are work motivation, self-efficacy, and leadership style. The purpose of this study was to analyze and explain the effect of work motivation, self-efficacy, and leadership style on employee performance at LPD Dalung Village. The population in this study were all employees working at the Dalung Village LPD, totaling 37 employees. The sampling technique in this study used a saturated sample technique. The sample in this study was taken from all employees working at the Dalung Village LPD, totaling 37 employees. Data collection methods used are documentation and questionnaires. The data analysis technique used in this study is multiple linear regression analysis. The results showed that work motivation (X1) had a positive and significant effect on employee performance (Y) at the Dalung Village LPD. Self efficacy (X2) has a positive and significant effect on employee performance (Y) at the Dalung Village LPD. Leadership style (X3) has a positive and significant effect on employee performance (Y) at the Dalung Village LPD.